2018
DOI: 10.1186/s12913-018-2977-1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the differential impact of individual and organizational factors on organizational commitment of physicians and nurses

Abstract: BackgroundPhysician and nursing shortages in acute and critical care settings require research on factors which might drive their commitment, an important predictor of absenteeism and turnover. However, the degree to which the commitment of a physician or a nurse is driven by individual or organizational characteristics in hospitals remains unclear. In addition, there is a need for a greater understanding of how antecedent-commitment relationships differ between both occupational groups.Based on recent finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 54 publications
4
42
0
1
Order By: Relevance
“…The discrepancy between the above results and the present study findings might be related to generally low organizational commitment level among the study participants, as larger organizations had a lower individual commitment. Moreover, lower commitment of intensive care staff in hospitals with more beds was indicated because of low salaries, OS, and critical care work conditions, which all apply to Abou Elreesh Teaching Children hospital …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The discrepancy between the above results and the present study findings might be related to generally low organizational commitment level among the study participants, as larger organizations had a lower individual commitment. Moreover, lower commitment of intensive care staff in hospitals with more beds was indicated because of low salaries, OS, and critical care work conditions, which all apply to Abou Elreesh Teaching Children hospital …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, lower commitment of intensive care staff in hospitals with more beds was indicated because of low salaries, OS, and critical care work conditions, which all apply to Abou Elreesh Teaching Children hospital. 27 Also, the current study showed that the commitment mean score was significantly higher in nurses than in physicians and that commitment score was significantly directly correlated to sources of stress score in nurses; however, no significant correlation was detected between them in physicians, a finding that could be explained by a study that examined the effect of stress on employees with different degrees of commitment and found that staff who had a high organizational commitment level experienced more stress than staff who were less committed. 28 Alternatively, other researchers as Kobasa and Antosrusk observed in 1998 that organizational commitment protected the individual from stress, either because committed individuals had connected strongly to the individuals at work or because they had found meaning in the work they do.…”
Section: Discussionmentioning
confidence: 99%
“…Autonomy has been defined as "the ability to choose how to do one's work; having influence over one's work; and flexibility in workload decisions" [23]. Autonomy is found to significantly and positively influence organizational commitment [12] [24]. Leadership empowerment in the form of autonomy on the job has a favorable effect on affective organizational commitment and turnover intentions [13].…”
Section: Job Autonomymentioning
confidence: 99%
“…Leadership empowerment in the form of autonomy on the job has a favorable effect on affective organizational commitment and turnover intentions [13]. A study of the relationship between autonomy and organizational commitment revealed that the degree of autonomy given on the job is a strong predictor of organizational commitment [24]. The provision of training and development to employees may result in a supervisor having more trust in the subordinate and granting him or her autonomy on the job.…”
Section: Job Autonomymentioning
confidence: 99%
“…In particular, the adjusted R 2 was examined in order to control the explanatory power of each model [56]. Three different models were developed, defining the influence of the different variables (control, independent and moderator variables), as suggested by other authors [3,57]:…”
Section: Discussionmentioning
confidence: 99%